A PV/T and Heat Pump based trigeneration system model for residential applications - Joyce, A (2011)
A solar trigeneration system, based on photovoltaic-thermal (PV/T) collectors, photovoltaic (PV) modules and a heat pump unit for heating and cooling, is modelled to forecast the thermal and electric yields of the system. The aim of the trigeneration system is to provide enough electricity, domestic hot water (DHW), heating and cooling power to meet the typical demand of an urban single family dwelling with limited roof area and allow the household to achieve a positive net energy status. The PV/T collectors and PV modules provide the electricity while the former also powers the DHW component of the trigeneration system. The heating and cooling components rely on a vapour compression cycle heat pump unit powered by electricity. In Fong et al. (2010), solar-powered electric compression refrigeration was found to have the most energy saving potential in subtropical climates. Thus, a heat pump based cooling system is a cost effective solution for residential applications in Lisbon,Portugal. Thus, according to the dwelling's location, construction details and energy demand patterns, the model computes the system's net results by comparing the dwelling demand with the trigeneration system supply. The paper presents a breakdown of the proposed trigeneration system model and describes each component briefly. Preliminary results produced by the model are presented and analysed in order to identify possible ways of improving the overall system performance.